2021
DOI: 10.1177/1420326x211010359
|View full text |Cite
|
Sign up to set email alerts
|

Renewal and upgrading of a courtyard building in the historic and cultural district of Beijing: Design concept of ‘multiple coexistence’ and a case study

Abstract: Historic buildings in urban areas are valuable heritage and would require effective design for renovation to upgrade these buildings while preserving their heritage characteristics. This current study evaluated renovation requirements: loss of natural and spatial characteristics, single function and lack of building facade design, of a courtyard building in a Beijing historical district. Limitations of the ‘multiple coexistence’ design concept were analysed to fully achieve integration of historical, cultural,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…20 Intelligent control strategies and equipment can effectively improve the comfort of courtyards during winter. 21 The application of adaptive building facades can improve the health of occupants, 22 and microclimate analysis methods can optimize the living conditions of historical buildings and also protect displayed artworks. 23 In addition, material selection, structural joints and technological applications are considered key factors for the success of heritage building restoration.…”
Section: Functional Adaptation Of Cultural Heritage In Built Environm...mentioning
confidence: 99%
“…20 Intelligent control strategies and equipment can effectively improve the comfort of courtyards during winter. 21 The application of adaptive building facades can improve the health of occupants, 22 and microclimate analysis methods can optimize the living conditions of historical buildings and also protect displayed artworks. 23 In addition, material selection, structural joints and technological applications are considered key factors for the success of heritage building restoration.…”
Section: Functional Adaptation Of Cultural Heritage In Built Environm...mentioning
confidence: 99%
“…It is necessary to explore how the various combinations of conditions lead to the sustainable development of urban renewal. Based on prior literature and on our observations, the antecedent conditions of this research contain the preservation of history and culture, differentiation, commercial publicity, project reformation and incremental innovation (Ye, 2019;Arbab et al, 2020;Guo et al, 2020;Che et al, 2021).…”
Section: Urban Renewalmentioning
confidence: 99%
“…Historic buildings in urban areas represent a valuable heritage which needs to be preserved throughout any improvement works (Che et al, 2021). The acceleration of urban update in recent years has caused serious damage to many historic environments, and large-scale demolition and destruction of historic environments have occurred in many cities.…”
Section: Preservation Of History and Culturementioning
confidence: 99%
“…However, there are relatively few studies on special areas such as historic districts. Recent studies on residential issues in historic and cultural districts have extensively investigated issues relevant to neighborhood environments [8], public service facilities [9,10], traffic problems [11], spatial characteristics [12], architectural styles [13][14][15], and neighborhood relations [16,17]. Settels [18], for example, found that newer communities are perceived to be less safe, accompanied by negative emotional signals such as depression and stress, and socioeconomically disadvantaged compared to older-established communities.…”
Section: Introductionmentioning
confidence: 99%